Rb-Sr dating of basement rocks from the southem foreland of the Mecsek Mountains, Southeastern Transdanubia, Hungary - Kovács Ádám (Acta mineralogica-petrographica, 1985)
Rb-Sr total rock and biotite age determinations have been carried out on samples from the borehole Baksa—2 disclosing sillimanite-grade metamorphic rocks of the Gorcsony Ridge (so called "Baksa Formation") at the northern margine of the Drava Basin in southeast Transdanubia. The 331 ± 13 Ma total rock isochron age is tentatively interpreted as the time of D! deformation immediately coupled to the dominant staurolite — kyanite — sillimanite grades (Barrowian) first phase of metamorphism. The overprinting second progressive metamorphic episod is characterized by high T medium P effects (D2 deformation) producing among others enstatite minerals in the ultramafics of Gyod as well as microgranitic-aplitic veins and segregations in the pelitic schists. Its age brackets of 331 and 315 Ma, followed by regional emergence and low-temperature retrograde effects probably due to prolongated uplift under low velocity conditions.